Beneficial impact of materials with reduced dimensionality on the stability of perovskite-based photovoltaics. (21st August 2019) - Petrović, Miloš; Rogdakis, Konstantinos; Kymakis, Emmanuel
Abstract: Organometallic lead-halide solar cells exhibited immense potential over the past years and reached the transition point from lab to industry-scale fabrication. However, bridging this gap and establishing perovskites as a viable competitor to conventional Si-based photovoltaics, hinges on the success of cost-effective upscaling process. The key factor impeding this transition is operational stability of solar cells under realistic photoconversion conditions. To this extent, reducing the dimensionality of cell constituents appears as a promising and very attractive approach to tackle this issue. The beneficial influence of such materials on device stability, which is explicitly tied to the engineered interface quality with underlying layers, comes as a result of complex interplay between energy alignment, strain-induced interactions and barrier-like properties of 2D components. The aim of this perspective is to briefly outline key challenges regarding the exploitation of 2D materials within the framework of perovskite photovoltaics, as well as to suggest further development directions.